2013
DOI: 10.1016/j.nedt.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Journal clubs: A two-site case study of nurses' continuing professional development

Abstract: Aim: This paper is a report on a study that explored the professional development of intensive care unit nurses in journal clubs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 51 publications
1
28
0
5
Order By: Relevance
“…The first item, critical appraisal of evidence from a research study may have been a result of reading the articles of the JC meeting itself. Studies have shown that JCs have an impact on EBP beliefs (Sciarra, 2011), confidence in reading research (LaChance, 2014;Honey & Baker, 2011;Nesbitt, 2013), and this project showed similar increase in reading research articles. Brown et al, 2008, found that one of the major barriers in implementing EBP was lack of confidence in appraisal of research articles, which JCs can help to alleviate.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The first item, critical appraisal of evidence from a research study may have been a result of reading the articles of the JC meeting itself. Studies have shown that JCs have an impact on EBP beliefs (Sciarra, 2011), confidence in reading research (LaChance, 2014;Honey & Baker, 2011;Nesbitt, 2013), and this project showed similar increase in reading research articles. Brown et al, 2008, found that one of the major barriers in implementing EBP was lack of confidence in appraisal of research articles, which JCs can help to alleviate.…”
Section: Discussionsupporting
confidence: 61%
“…The other two items showing statistically significant improvement were increase in informal discussion of evidence from a research study and the promotion of the use of EBP with a colleague was also observed by Nesbitt (2013). More specifically, there was not a measurable increase in using evidence to change individual practice, as was shown by Wilson (2015).The answers to questions that did not show a positive change may be related to need for more education on EBP to staff nurses and the role every nurse plays in finding this evidence.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…8 Interventions that improved attitudes were EBP/research councils, 9 journal clubs, 14 critical appraisal seminars, 10 EBP workshops with co-interventions like opinion leaders, 5 or formal immersion programs. 6,12,13 Qualitative evidence confirmed that educational programs opened nurses' minds about the value that research brings to practice.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses expressed broadened worldviews and renewed empowerment and accountability to question and reflect on their practice. [12][13][14] For knowledge and skills, written instructions assisted clinicians in developing correct PICO questions. 5 One-day seminars significantly increased critical appraisal knowledge.…”
Section: Resultsmentioning
confidence: 99%